MATHEMATICAL MODELING REGIME STEADY STATE FOR DOMESTIC WASTEWATER TREATMENT FACULTATIVE STABILIZATION PONDS - Sunarsih Sunarsih; Purwanto Purwanto; Wahyu Setia Budi (Journal of Urban and Environmental Engineering, 2013)
This paper presents a model for natural syst ems used in Wastewater Treatment Plant (WWTP) Sewon Bantul. The model is m odeling development, derived from the physical and biochemical phenomena involved in the biological treatment process. The numerical solution of the resulting on 13 simultaneous systems of nonlinear equations by the Quasi_Newton. Data validation is measured by facultative pond at the inlet and outlet of the pond to the concentration of b acteria, algae, zooplankton, organic matter, detritus, organic nitrogen, NH3, organi c phosphor, dissolved phosphorus, Dissolved Oxygen (DO), total coliform, faecal coliform and Biochemical Oxygen Demand (BOD). A simulation model is presented to predict performance regime steady state of domestic wastewater treatment facultative stabilization pond. The high degree of significant of at least 10% indicates that the effluent parameters can be reasonably accurately predicted.